Embracing Mechanobiology in Next Generation Organ-On-A-Chip Models of Bone Metastasis - Slay, Ellen E.; Meldrum, Fiona C.; Pensabene, Virginia; Amer, Mahetab H. (Frontiers in Medical Technology, 2021)
Bone metastasis in breast cancer is associated with high mortality. Biomechanical cues presented by the extracellular matrix play a vital role in driving cancer metastasis. The lack of in vitro models that recapitulate the mechanical aspects of the in vivo microenvironment hinders the development of novel targeted therapies. Organ-on-a-chip (OOAC) platforms have recently emerged as a new generation of in vitro models that can mimic cell-cell interactions, enable control over fluid flow and allow the introduction of mechanical cues. Biomaterials used within OOAC platforms can determine the physical microenvironment that cells reside in and affect their behavior, adhesion, and localization. Refining the design of OOAC platforms to recreate microenvironmental regulation of metastasis and probe cell-matrix interactions will advance our understanding of breast cancer metastasis and support the development of next-generation metastasis-on-a-chip platforms. In this mini-review, we discuss the role of mechanobiology on the behavior of breast cancer and bone-residing cells, summarize the current capabilities of OOAC platforms for modeling breast cancer metastasis to bone, and highlight design opportunities offered by the incorporation of mechanobiological cues in these platforms.